Spatiotemporal and genomic analysis of carbapenem resistance elements in Enterobacterales from hospital inpatients and natural water ecosystems of an Irish city - Mark Maguire; Carlos Serna; Natalia Montero Serra; Aneta Kovarova; Louise O’Connor; Niamh Cahill; Brigid Hooban; Niall DeLappe; Wendy Brennan; Genevieve Devane; Martin Cormican; Dearbháile Morris; et al. (Microbiology Spectrum, 2025)
ABSTRACT Carbapenemase-producing Enterobacterales (CPE) is a diverse group of often multidrug-resistant organisms. Surveillance and control of infections are complicated due to the inter-species spread of carbapenemase-encoding genes (CEGs) on mobile genetic elements (MGEs), including plasmids and transposons. Due to wastewater discharges, urban water ecosystems represent a known reservoir of CPE. However, the dynamics of carbapenemase-bearing MGE dissemination between Enterobacterales in humans and environmental waters are poorly understood. We carried out whole-genome sequencing, combining short- and long-sequencing reads to enable complete characterization of CPE isolated from patients, wastewaters, and natural waters between 2018 and 2020 in Galway, Ireland. Isolates were selected based on their carriage of Class A blaKPC-2 (n = 6), Class B blaNDM-5 (n = 12), and Class D blaOXA-48 (n = 21) CEGs. CEGs were plasmid-borne in all but two isolates. OXA-48 dissemination was associated with a 64 kb IncL plasmid (62%), in a broad range of Enterobacterales isolates from both niches. Conversely, blaKPC-2 and blaNDM-5 genes were usually carried on larger and more variable multireplicon IncF plasmids in Klebsiella pneumoniae and Escherichia coli, respectively. In every isolate, each CEG was surrounded by a gene-specific common genetic environment which constituted part, or all, of a transposable element that was present in both plasmids and the bacterial chromosome. Transposons Tn1999 and Tn4401 were associated with blaOXA-48 and blaKPC-2, respectively, while blaNDM-5 was associated with variable IS26 bound composite transposons, usually containing a class 1 integron.IMPORTANCESince 2018, the Irish National Carbapenemase-Producing Enterobacterales (CPE) Reference Laboratory Service at University Hospital Galway has performed whole-genome sequencing on suspected and confirmed CPE from clinical specimens as well as patient and environmental screening isolates. Understanding the dynamics of CPE and carbapenemase-encoding gene encoding mobile genetic element (MGE) flux between human and environmental reservoirs is important for One Health surveillance of these priority organisms. We employed hybrid assembly approaches for improved resolution of CPE genomic surveillance, typing, and plasmid characterization. We analyzed a diverse collection of human (n = 17) and environmental isolates (n = 22) and found common MGE across multiple species and in different ecological niches. The conjugation ability and frequency of a subset of these plasmids were demonstrated to be affected by the presence or absence of necessary conjugation genes and by plasmid size. We characterize several MGE at play in the local dissemination of carbapenemase genes. This may facilitate their future detection in the clinical laboratory.